Transfer of Land Functions and Social Functions of Land Rights in Indonesia - Murhaini, Suriansyah; Ludang, Yetrie (Advances in Social Sciences Research Journal, 2019)
This paper discussed understanding the social function of land rights, existence of land in the context of social change and social shift, relationships, social functions of land rights with public interests, land procurement in relation to social functions, and the role of enforcing the social function of land rights. In addition, agrarian reform in Indonesia is also discussed includes understanding, objectives, subjects and objects, principles, mechanism and failure in implementing agrarian reform. Moreover, this paper discussed the practice of diversion function of agricultural land, including the understanding of land and transfer of functions land, factors that drive the transfer of use functions land, abuse of land use change and transfer impacts the function of agricultural land on people’s lives.